Management and Outcome of AKI in Patients with Cirrhosis (Academia Journal of Medicine, 2020)
Background: The increased propensity for AKI in patients with cirrhosis stems from hemodynamic abnormalities typical of patients with  cirrhosis and ascites15 which is due to development of portal hypertension and portosystemic collaterals with splanchnic and systemic  vasodilatation , resulting in decrease in effective arterial blood volume with increase in renin angiotensin- aldosterone system (RAAS), sympathetic nervous system, and non osmotic release of antidiuretic hormone causing sodium retention, increased intravascular volume, and a  hyperdynamic circulatory state16 complemented with increased production of nitric oxide which is considered the main cause of vasodilatation  in cirrhosis. Subjects and Methods: All participating patients of either gender admitted in department of Gastroenterology at Tertiary care  hospital with age >18 years with either diagnosed or newly diagnosed case of cirrhosis of liver( including both compensated & decompensated  cases ) admitted with acute kidney injury diagnosed according to International Club of Ascites Classification were enrolled in this study. Results: Among 26 patients requiring hemodialysis , 10 ( 38.5 %) of patients recovered from hemodialysis whereas 16 ( 61.5 %) of patients  didn’t recovered from hemodialysis & either died on hemodialysis or was discharged on hemodialysis which needs to be continued. Conclusion: Totally 25.5 % of patients expired during course of treatment in hospital whereas 74.5 % were survived the hospital stay.
Keywords: Outcome; AKI; Cirrhosis